Strengthening BUMDES Management to Build Independently Through MSMEs in Increasing Village Income - Syafrizal Syafrizal; Siti Hajar; Kholilul Kholik (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The establishment of the BUMDes Bangun Mandiri Desa Bekiung aims to provide benefits to the village community and also to increase village income through the development of village potential carried out by BUMDes. There are several excellent programs that have been implemented well through BUMDes management, including Savings and Loans Unit Cooperatives, agriculture and animal husbandry. These programs aim to provide MSMEs with benefits to rural communities in improving their welfare. The development of the economic and trade sectors has also been carried out through the provision of rice and basic needs for rural communities. So, to support this program, a Village Micro, Small and Medium Unit (UMKM) is needed that can distribute village results obtained from the community so that it can increase village income. This activity is carried out in several stages, as follows: 1) The socialization stage which aims to provide information about MSMEs to the public through BUMDES; 2) Stages of mentoring and training related to marketing and promotion management, development of product processing and packaging. The results obtained in this PKM activity are increasing public understanding of the importance of MSMEs in developing village potential under the supervision of BUMDes so that village potential results can be promoted and creating separate business innovations such as processing animal feed through the cultivation of caterpillars and worms